The Role of Contemporary Temporomandibular Joint Imaging Modalities in Long-Term Occlusal Rehabilitation - Mirza, Р. О.; Biloklytska, Г. Ф. (Actual Dentistry, 2025)
Actuality. Computed tomography (CT) is paramount in evaluating morphological changes in the articular eminence and condylar head osseous structures and assessing their spatial relationships. The International Classification of TMJ Disorders has established a distinct categorization of internal derangements based primarily on magnetic resonance imaging (MRI) findings rather than CT imaging. Treatment outcome analyses incorporating both imaging modalities demonstrate superior diagnostic value and prognostic capability. Aim: to characterize the osseous relationships within the temporomandibular joint complex to classify internal derangements through concurrent MRI and CT imaging analysis performed in therapeutic jaw positions. Material and methods. 55 magnetic resonance imaging (MRI) and computed tomography (CT) scans of the temporomandibular joint (TMJ) were performed following gnathological splint therapy. On the CT scans, the anterior and superior joint spaces were measured in the therapeutic maxillomandibular relationship, with the obtained values presented as dimensional ratios. A comprehensive clinical examination was conducted to determine the presence of mandibular deflection and to classify the type of TMJ clicking sounds. MRI scans, particularly those obtained in the open-mouth position, were utilized for supplementary analysis of the efficacy of conservative treatment for temporomandibular disorder (TMD). Results. Internal derangements identified through MRI in therapeutic jaw positions, specifically disc displacement without reduction and limited opening, did not necessarily manifest clinically as joint clicking. TMJ dysfunction presenting with limited opening demonstrated more pronounced mandibular deflection patterns (lateral deviation during opening) in cases where complete disc reduction was visualized contralaterally in maximum opening. Conclusion. A notable clinical observation in managing TMJ dysfunction using gnathological splints is the potential for diagnostic category transitions. Patients initially presenting with disc displacement or disc displacement with reduction and intermittent locking may transition to the category of normal disc position with reduction following treatment. Furthermore, patients diagnosed pre-treatment with disc displacement without reduction with limited opening may, following muscle deprogramming, transition to various categories, including disc displacement without reduction without limited opening, disc displacement without reduction with limited opening, and normal disc position with reduction.